Conviction - Mina, Denise (Mulholland Books, Little, Brown and Company, 2019)
An upper-class Edinburgh housewife who enjoys listening to the sordid details of true-crime podcasts has her world turned upside down when a new podcast turns out to have connections to her own dark past.